2017
DOI: 10.1007/s00421-017-3657-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of progressive resistance training and weight loss versus weight loss alone on inflammatory and endothelial biomarkers in older adults with type 2 diabetes

Abstract: Long-term participation in PRT, independent of change in weight, can result in some improvements in certain inflammatory markers in older overweight adults with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 54 publications
1
21
0
1
Order By: Relevance
“…Briefly, taking higher dose of vitamin D may be required to affect diabetes risk and control high levels of inflammatory factors in patients with T2D and vitamin D deficiency [1]. Consistent with that, Miller, et al [29] reported that in diabetic and overweight elderly patients participating in resistance training, 3 times a week for 12 weeks, some inflammatory markers significantly improved.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Briefly, taking higher dose of vitamin D may be required to affect diabetes risk and control high levels of inflammatory factors in patients with T2D and vitamin D deficiency [1]. Consistent with that, Miller, et al [29] reported that in diabetic and overweight elderly patients participating in resistance training, 3 times a week for 12 weeks, some inflammatory markers significantly improved.…”
Section: Discussionmentioning
confidence: 84%
“…As previously mentioned, both vitamin D [4] and physical activity [29] are believed to affect systemic inflammation in diabetic people. It has been reported that increased serum 25(OH) D levels in diabetics improves inflammatory markers and glycemic control [28].…”
Section: Discussionmentioning
confidence: 92%
“…After screening the titles of the rest of the 2421 articles, 288 were selected for the abstract and full-text assessment, and 37 of them were included in this study, which met the required inclusion criteria. Out of 37, 13 articles were excluded with the following reasons: control group was not diabetic in three trials [23,24,25], data presented as mean difference or no comparable diabetic control trial in seven studies [13,15,23,26,27,28,29], two articles with insufficient exercise intensity details [30,31] and same data used in different articles [32]. Finally, 24 articles [19,20,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54] were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Mokhtarzade et al reported that leptin and tumor necrosis factor (TNF)-α levels significantly decreased subsequent to aerobic interval training [24]. Miller et al reported that serum adiponectin levels were increased, and serum interleukin 10 and TNF-α levels were decreased in a high-intensity progressive resistance training with moderate weight loss group, compared to the weight loss group, in older overweight adults with type 2 diabetes after 12 months [25]. This shows that long-term participation in exercise training, irrespective of change in weight, can improve certain inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%